Response to the Comments of Casabianca et al. (2025). - Moraes, Cicero (Archaeometry, 2026)
The response to the comments of Casabianca et al. (2025) aims to clarify interpretive misconceptions and reaffirm the methodological coherence of the study Image Formation on the Holy Shroud—A Digital 3D Approach. The presented criticisms disregard the declared scope of the research, which is strictly methodological in nature, focused on evaluating morphological deformation in the projection of the body onto fabric. The exclusive use of the frontal region, the choice of visual sources, and the historical contextualization based on tomb effigies are consistent with the proposed objective and find precedent studies. The response emphasizes the transparency of the data, the replicability of the experiment, and the legitimacy of the adopted scientific approach, refuting the allegations of conceptual or historical flaws.